BLENDED TEACHING OF FOREIGN LANGUAGE IN CHINA FROM THE PERSPECTIVE OF ECOLOGY - Linlin, Song (PUPIL: International Journal of Teaching, Education and Learning, 2021)
It has been 15 years since the theories in ecology had been introduced to foreign language education in China. Researches from the ecological perspective on blended teaching of a foreign language are also thriving as the educational technologies are ever enhanced. In this study, the related CNKI (China National Knowledge Infrastructure) literature from 2010-2020 was collected, and CiteSpace was employed to review the exploration of the research hot-spots, trends, and limitations in this area. The results indicate that 1. in China, the main methods to realize the blended teaching are flipped classroom and MOOC; 2. a majority of the macroscopic researches are conducted to build an ecological mode for college English and higher vocational English while the microscopic researches are for teachers’ and students’ ecological niches; 3. with the advent of “Internet Plus” age, researches in China will march on to the “smart” ecology of blended foreign language education.; 4. though the studies are involved in diverse directions, there are limitations in this field due to a late start.